Improvement of the Methodology for the Justification of Retail Prices for Oil Products - Lenkova, Olga Viktorovna (International Journal of Energy Economics and Policy, 2017)
The purpose of this article is the development of the methodological tool for the formation of retail prices for oil products at the oil products supply (OPS) organization with regard to the regional industrial specifics and market conditions. The stated purpose predetermined the need for the consistent solution of the following tasks: the characteristic of the current pricing system at the OPS organization; the development of recommendations on the improvement of the efficiency of the pricing mechanism for fuel products; the approbation of the proposed methodological recommendations on the formation of retail prices for fuel products of the OPS organization. The article provides the results of the study of the practice of setting retail prices for target products by the OPS organizations. The article identifies the trends of the improvement of the current methodological tool, namely the possibility of accounting regional industrial features of the operation of appropriate sales organizations when justifying prices for oil products. The article offers the authorial approach to the setting of retail prices, which allows envisaging such factors as the level of consumer welfare in the local territory and the sensitivity of consumers to the price change (elasticity), and also the competitiveness level of the organization at the specific regional level. The article provides the results of the approbation of methodological recommendations. Keywords: the price, oil products, well-being of the population, competitiveness of the organization, price elasticity JEL Classifications: D41, D60, O33